Effect of Delay in Postpartum Hemorrhage Management on the Rate of Near-Miss and Maternal Death Cases - Siswosudarmo, Risanto (Indonesian Socety of Obstetrics and Gynecology, 2014)
Objective: To recognize the effect of delay in the management of postpartum bleeding to the occurrence of near-miss and maternal death cases. Method: Prospective cohort. The study population was patients with postpartum hemorrhage. All PPH cases from thirteen hospitals (Sardjito and 12 affiliated hospitals) were recorded. The study was carried out from January 1st to June 30th 2009. The study group was those who experienced delay and the control group was those withoutdelay. The outcome was measured as the number of near-miss and death cases. Near-miss was defined as those who experienced severe shock, demonstrated by systolic blood pressure 90 mmHg or less. Chi square test, t-test and logistic regressions were used to analyze our data.Result: From January 1st to June 30th 2009 we identified 139 cases of PPH from 8,924 deliveries (1.6%). From the 80 referred cases, as much as 22 cases (27.5%) were delayed, and 12 from 139 (8.6%) experienced delay in the hospital. A total of 30 cases among 139 (21.6%) experienced delay both outside and in the hospital. There were 74 near-miss cases, 9 of which ended in death of the patient. This means the real occurrence of near-miss cases is 65 from 139 cases or 46.8% while the occurrence of maternal death was 9 out of 139, or 6.47%. Case fatality rate was 9 from 139 or 6.47%; maternal near-miss ratio was 6.22; mortality index was 13.84% and maternal mortality ratio is estimated as 103/100.000 live births. Multivariate analysis showed delay in referral increased the risk of near-miss cases as much as 8.37 folds, while bleeding >1500 ml increased risk of near-miss by 12.12 folds. Delay in both referral and management in the hospital increased the risk of maternal death rate as much as 25.34 folds, hemoglobin <6 g/dl and unavailability of blood increase maternal death by 31.58 folds and 13.39 folds, respectively.Conclusion: Delay in referral and delay of in-hospital management ncreased the occurrence of near-miss and maternal mortality cases significantly. Multivariate analysis showed that the amount of bleeding, hemoglobin level and lack of blood availability influenced the occurrence of near-miss and maternal death more than the delay itself.Keywords: delay, maternal death, maternal near-miss, PPH